Capillary pressure of a continuous gas–oil–water flow in a horizontal micron capillary. Issue 16 (17th August 2016) - Zhou, W. J.; Gao, C. N.; Lu, Y. C.; Wang, Z. C.; Wu, P. C.; Li, X. F.; Dong, J. F.
ABSTRACT: Capillary pressure is one of the most important factors in characterizing the fluid behavior in a wide variety of processes with environmental and energy concerns. In this paper, Washburn equation is extended to describe the displacement kinetics of the continuous gas–oil–water flow in a single horizontal tube. Experimental investigations of the continuous two- and three-phase flows in capillaries with diameters of 2–10 μm were performed to study the effect of the capillary pressure on their fluid behavior. The results indicate that the total capillary pressure of a continuous three-phase flow is affected by the combined action of the two fluid interfaces presented: gas–liquid and liquid–liquid interfaces.